2017
DOI: 10.1016/j.jtcvs.2017.03.048
|View full text |Cite
|
Sign up to set email alerts
|

The no-touch saphenous vein graft in elderly coronary bypass patients with multiple comorbidities is a promising conduit to substitute the left internal thoracic artery

Abstract: In elderly coronary bypass patients with multiple comorbidities, a no-touch saphenous vein graft is a promising substitute for the left internal thoracic artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
2
17
1
1
Order By: Relevance
“…Subsequently, a randomized trial comparing C SVG and NT SVG has shown that the latter is superior in terms of patency rates and left ventricular ejection fraction at 1.5, 8.5, and 16 years postoperatively [15][16][17][18] , as seen in Table 1 from Samano et al [17] , 2015. Furthermore, NT SVGs exhibit a patency comparable to that of LITA at up to 16 years [16,17,19] , as seen in Figure 1 from Samano et al [17] , 2015.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 77%
“…Subsequently, a randomized trial comparing C SVG and NT SVG has shown that the latter is superior in terms of patency rates and left ventricular ejection fraction at 1.5, 8.5, and 16 years postoperatively [15][16][17][18] , as seen in Table 1 from Samano et al [17] , 2015. Furthermore, NT SVGs exhibit a patency comparable to that of LITA at up to 16 years [16,17,19] , as seen in Figure 1 from Samano et al [17] , 2015.…”
Section: Saphenous Vein Structure and Vascular Damagementioning
confidence: 77%
“…The no-touch technique in harvesting the saphenous vein consists of several steps in order to get a good quality conduit as well as to reduce leg wound complications (Video 1). Previous studies have shown a superior patency for the no-touch vein grafts in both the short- and long-term [1-4] .…”
Section: Surgical Techniquementioning
confidence: 99%
“…This technique has been shown to reduce the risk of spasm and the need for distension (23) and consequently, preserves vessel wall integrity (20). This technique provides a superior patency rate (25)(26)(27)(28), preserved left ventricular function (29), and a better clinical outcome (30) compared to conventional harvesting, in both the short and the long term.…”
Section: No-touch (Nt) Harvesting Techniquementioning
confidence: 99%